Potential climate risks in financial markets: Report from a workshop, January 20, 2016 - Ingrid Hjort (University of Oslo, Department of Economics, 2016)
Climate change has the potential to affect the global economy through physical impacts, but may also initiate regulations, policies, as well as technological innovation. Over time climate science and environmental economics have developed a better understanding of the potential impact over a variety of scenarios. The economic impacts on sector, industries and market are still uncertain, making the timing and the extent of impact difficult to predict in detail. As climate change might affect the global economy, risks in financial markets increase. The academic literature on financial economics of climate change is limited. The implications for financial markets of climate change seem not to have been addressed extensively in the literature. The workshop on Potential climate risks in financial markets gathered a selected group of scholars from finance, macroeconomics, microeconomics and resource & environmental economics, to explore and discuss the potential financial impacts from climate change.
Keywords: 330